Biosafety in dental surgical procedures in front of the COVID-19 pandemic (Research, Society and Development, 2021)
Biosafety measures intensified after the beginning of the COVID-19 pandemic, which is a disease that can develop a clinical picture ranging from asymptomatic infections to severe respiratory conditions. Thus, dental surgeons, as well as other health professionals, had to adapt to stricter criteria for dressing. The objective of this study is to present the main recommendations regarding biosafety in dental surgical procedures in the face of the pandemic. This work is a systematic review of the literature, carried out through articles published in English, Spanish and Portuguese, between 2010 and 2020, published in the PUBMED, BVS, RESEARCH GATE, SCIELO databases, with the following descriptors: oral surgery, biosafety, COVID-19. It was found that the specialty of Buccomaxillofacial Surgery and Traumatology is the most exposed to the risks of infections by bioaerosols, and due to this, the use of surgical masks is necessary, PFF2 / N-95, faceshields, goggles and disposable cloak, as well as the adoption of strict protocols for hygiene, disinfection, sterilization, and organization of the surgical environment, whereas Teledentistry proved to be a viable auxiliary instrument in this period in order to reduce the risks to exposure by SARS-CoV-2. The professional who works in urgent and emergency surgical care must follow the biosafety measures issued by the health surveillance agencies in order to ensure that the worker's health is guaranteed, as well as that of the patient.